Hydrometeorological hazard prediction in the kuto bodri river region central java based on normalized difference vegetation index (ndvi) analysis. Issue 1 (March 2021) - Basuki, Y; Widjonarko
Abstract: The objective of this paper is to predict drought as a hydrometeorological hazard to anticipate the lack of water in Kuto Bodri River Region. The method based on Normalized Difference Vegetation Index (NDVI) analysis. Drought assessment based on the assumption of photosynthetic. If photosynthesis goes well, it indicates that enough water is available to support the process. The data is using Landsat 8 image from March to October 2018. The results show that the potential of drought occurs in the Kuto Bodri River Area in the September-April period. The NDVI value in the period shows a low number, the pattern of distribution of NDVI with a low value is quite even and even in the upstream region which in fact is a forest area NDVI value shows a minus number, meaning photosynthesis does not run well and indicates the availability of water is minimal. The potential drought threat in the Kuto Bodri WS began in June 2018 to October 2018 and occur in the downstream area, especially in the type of paddy fields. Based on this result it is necesary to make policy to anticipate and overcome this hazard such as sosialization in farmer community.